2013
DOI: 10.1039/c3cp50361e
|View full text |Cite
|
Sign up to set email alerts
|

Selective catalytic oxidation using supported gold–platinum and palladium–platinum nanoalloys prepared by sol-immobilisation

Abstract: Supported nano-alloys have been prepared using the sol-immobilisation method for two bimetallic combinations, namely gold-platinum and palladium-platinum, using activated carbon and titania as supports. Some of the materials were prepared using a method where both metals are simultaneously reduced, thereby leading to homogeneous alloys being formed. In addition, sequential reduction of the metal combinations has also been investigated to facilitate the formation of core-shell structures. The materials have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 25 publications
1
34
1
2
Order By: Relevance
“…Previous studies showed that bimetallic nanoparticles are formed as a homogeneous alloy if Au and Pd are reduced simultaneously during the preparation of the catalyst. [21] The fact that the measured Au/Pd surface ratios are close to 1 (Table 3) agrees with this observation. The relative concentration of surface carbon is also displayed in Table 3.…”
Section: Sol_2xpva_ref90supporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies showed that bimetallic nanoparticles are formed as a homogeneous alloy if Au and Pd are reduced simultaneously during the preparation of the catalyst. [21] The fact that the measured Au/Pd surface ratios are close to 1 (Table 3) agrees with this observation. The relative concentration of surface carbon is also displayed in Table 3.…”
Section: Sol_2xpva_ref90supporting
confidence: 84%
“…Such a synergistic effect between Au and Pd has already been observed in other oxidation reactions such as benzyl alcohol oxidation. [21] This phenomenon has been ascribed to Au atoms drawing electron density away from Pd atoms, which thus en- hances the interaction of Pd with the reactants. [22] In relation to product distribution, Au nanoparticles gave the highest selectivity towards butyl butyrate, which is formed from the esterification of n-butanol and butyric acid.…”
Section: Resultsmentioning
confidence: 99%
“…Even though these studies were not focused on catalysis, they proved the feasibility of imaging various Au-based alloys by FIM; alloys which are now used for catalysis applications: AuMo [228] for the reverse water-gas shift reaction [229,230] or as N2 dissociation catalyst for the HaberBosch process [231], Au-Pt [224] for CO oxidation [49,232] and selective toluene oxidation [52], AuFe [226] for CO oxidation [233] and N2 dissociation catalyst for the Haber-Bosch process [231], and Au-Cu [225,234] for the water gas-shift reaction [235,236] and CO oxidation [50].…”
Section: Perspectivesmentioning
confidence: 99%
“…In addition to this, a decreased size of the particles increases the dispersion, and accordingly the number of edges and kinks on the metallic particles: such highly uncoordinated surface sites could correspond to the preferential adsorption sites, and their increasing number could then be responsible for the increasing reactivity of the catalytic materials. During the last decade, the research on catalytic materials with gold mainly focuses on the development of bimetallic gold-based catalysts [48][49][50][51][52]. Indeed, the use of bimetallic catalysts allows, to some extent, the size sensitivity of gold catalysts to be diminished.…”
Section: Introductionmentioning
confidence: 99%
“…[30,31] The total metal loading used here was 1 wt.%. For bimetallic AuPd catalyst, the weight percentages of Au and Pd were both 0.5 wt%.…”
Section: Catalyst Preparationmentioning
confidence: 99%